Physical frailty and cognitive status over-60 age populations: A systematic review with meta-analysis. (September 2018) - Furtado, Guilherme Eustáquio; Caldo, Adriana; Rieping, Taís; Filaire, Edith; Hogervorst, Eef; Teixeira, Ana Maria Botelho; Ferreira, José Pedro
Graphical abstract: Highlights: Physical and cognitive frailty seems to follow a similar pattern of progress. Policies for active aging should be improved in several countries. Abstract: The aim of this meta-analysis was to analyse the magnitude of the effect-size of the cognitive status of populations over 60 years of age, when comparing nonfrail versus pre-frail and nonfrail versus frail subgroups. A systematic review of prospective studies published from 2000 to 2017 was completed in Medline, B-on, Ebsco, Ebsco Health, Scielo, ERIC, LILACS and Sport discus databases and observational, cohort and cross-sectional studies were selected. The Mini-Mental State Examination to screening cognitive status and the Fried phenotype for assess physical frailty state was used as clinical outcomes. After applying additional search criteria, 14 manuscripts (26, 798 old participants) were selected from an initial universe of 1681 identified. When comparing the scores of cognitive status of the participants who were non-frail (n = 12, 729, 47.4%) versus pre-frail (n = 11, 559, 43.2%) and non-frail versus frail (n = 2452, 9.4%) subgroups, significant statistical differences were found for both comparisons (M ± SD = 0.60, 95%CI: 0.50-0.62, p < 0.001 and M ± SD = 3.43, 95%CI: 2.26–4.60, p < 0.001, respectively). It is clear that poor cognitive function is strongly closed associated with pre-frailty and frailty subgroups in older populations around the world.